Chemical and process plant commissioning handbook : a practical guide to plant system and equipment installation and commissioning - Killcross, Martin (Butterworth-Heinemann, 2012)
The Chemical and Process Plant Commissioning Handbook is a must have for engineers in the chemical process and process plant sectors, or for those refreshing their skills in this area. It provides a guide and reference to preparing a systematic methodology for converting a newly constructed plant, as well as streamlining equipment into an operational process unit. Includes downloadable commissioning process checklists that comply with industry standard best practice which readers can use and adapt for their own situations. The reference focuses on the critical safety assessment and inspection regimes necessary to ensure that new plants are compliant with OSH(A) and environmental requirements. Martin Killcross has brought together the theory of textbooks/Perry's and technical information obtained from sales literature, in order to provide engineers with what they need to know before initiating talks with vendors regarding equipment selection. Delivers the know-how to succeed for anyone commissioning a new plant or equipment. Comes with online commissioning process templates which make this title a working tool kit. Extensive examples of successful commissioning processes included, and step-by-step guidance to assist understanding of the wide range of tasks required in the commissioning process.